Pengaruh Fasilitas Wisata dan Harga Terhadap Keputusan Berkunjung Wisatawan di Wana Wisata Batu Kuda Kabupaten Bandung - Negara Bayu Mahendra; Zia Kemala (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
The research aims found out and explained the influence of tourist facilities and prices on the decision to visit tourists in Wana Wisata Batu Kuda. The study used quantitative methods with descriptive analysis and verificative analysis. The population in this study the sample used was 100 respondents. The data collection technique used a questionnaire (questionnaire) by distributing questionnaires to samples (respondents) and collecting them again for processing. The analytical method used was instrument test (validity test, reliability test, normality test and linearity test), descriptive analysis, multiple regression analysis, coefficient of determination, t test, and F test using IBM SPSS 24 for Windows. The results of this study indicated that all question items are valid and reliable. Facilities and prices partially and simultaneously influence the decision to visit tourists at Wana Wisata Batu Kuda. The conclusion of this study is that facilities and prices have a positive and significant effect on the decision to visit tourists at Wana Wisata Batu Kuda.